On derivative consequence argument - D. N. Razeev (Омский научный вестник: Серия "Общество. История. Современность")
The article gives critical remarks to the derivative consequence argument proposed by Bogdan Faul. The first critical remark concerns the ontological status of the laws of nature, the second remark deals with the term «physicalism». It is demonstrated that conceptual vagueness of the terms used by B. Faul in his article undermines the validity of the proposed derivative argument